Enhancing healthcare cost transparency: assessing implementation challenges, criticisms, and alternative solutions - Malik, Sonia Ali (Frontiers in Health Services, 2025)
The United States healthcare system grapples with a staggering estimated waste of 935 billion, with pricing failure contributing a substantial 240.5 billion. This paper explores an innovative solution to combat rapidly escalating healthcare costs by proposing measures that would complement the mandated disclosure of healthcare prices. The Centers for Medicare and Medicaid Services (CMS) introduced a significant rule for hospital pricing, effective January 1, 2021, aiming to enhance transparency and empower patients to make value-based decisions. However, this rule has faced criticisms on various policy grounds which this examination delves into. To address these concerns and enhance the effectiveness of price transparency, this paper suggests complementary and/or alternative strategies and solutions while also examining the engagement of enrollees in price transparency tools.